FUNDAMENTALS OF DEVELOPING CIVIL AND COMMUNITY COMPETENCES IN STUDENTS - Kandaharov Kahramon Hasanovich (Scholar Express Journal, 2022)
This article analyzes the pedagogical and psychological aspects of the use of the electronic environment in the development of civic and intercultural competencies in students, the use of the electronic environment in the development of civic and intercultural competencies in students , improving the quality and effectiveness of vocational training. The process of using the electronic environment to develop civic competencies in students by optimizing the requirements of social competence to the requirements of social order is also presented
Keywords: Legal Consciousness; Legal Culture; Civic Position; Competence